RANCANG BANGUN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA PT SAMATOR GAS INDUSTRI - Abdul Hayat; Umi Riyandho (LPPM Unbaja, 2019)
Sales function is one of the most important elements and has a direct effect on the sustainabilityof a company. An effective and efficient sales system will determine the success of the company'sperformance. PT Samator Gas Industri (SGI) is a retail company engaged in the trading of thegas and medical gas industry. The existing sales transaction that has been running so far is stillconventional, in this case the customer only uses telephone media or comes directly to thepurchase process and the order payment process is done in cash. The way of existing salestransaction has several gaps for improvement regarding to improve services to PT SGI’scustomers. This study aims to create a sales information system design at PT Samator GasIndustri. The method used to design the sales information system is the System Development LifeCycle (SDLC) approach. To analyze the system gap, PIECES analysis is used, while the toolsused for modeling and system design are Unified Modeling Language (UML), PhP programminglanguage and MySQL database. The sales information system of the design results has featuressuch as Sales Order, Payment, Sales Administration, Sales Invoice, and others.